High Touch Approach and Its Relationship with Students’ Learning Outcomes at IAIN Bukittinggi - Darul Ilmi (AT-TA'LIM, 2017)
Learning without students’ center tends to create less passionate students in following the lecture. They tend to ignore their lecturer. They have less attention, and try to create ineffective conditions, therefore, the learning atmosphere will become less effective to achieve the intended goals.  The purpose of the research is to determine the process of learning, the implementation of High Touch approach, and factors that influence its implementation. Classroom action research approach was used at  department of mathematics which involve students who enroll at academic year 2016/2017 IAIN Bukittinggi. The research was done in two cycles in which one cycle conducted three meetings. The instruments used were observation, essay questions, and tasks given to students. The results show that there is an improvement in students’ participation and activeness in learning when their lecturer builds learning experience through reinforcement, affection, guide, directive action, and good modeling by student–center andself-learning activities, and independent learning skill orientations showed in cycle I and II. It implies that implementing high touch may lead students to be more active, creative, and fun in learning.